Técnica de regularização baseada no índice de incoerência geológica para inversão de dados sísmicos - Souza, Raphael Vieira Menezes de (2018)
This work advances the use of the Full Waveform Inversion technique (FWI) in the generation of images based on the complete wave equation. In this technique, from the information of the transit time and amplitude of the signal, obtained from a seismic survey, it is possible to generate images that represent the physical properties in subsurface. In the present work, the direct problem will be modeled by the Helmholtz equation for the frequency domain, and solved by the Finite Difference Method, and the inverse problem will be solved by a multi-scale strategy. The main objective of this thesis is the use of the Geological Incoherence Index - IIG as a restriction in the process of regularization of the inverse problem. Computational experiments showed that the use of IIG as a link carrying information related to sedimentary bedding, directed the solution of the problem to a more geologically probable solution, providing more realistic images of the subsurface compared to the classic FWI.